MEDIA EDUKASI VIDEO ANIMASI “CERDIK” DALAM PENCEGAHAN DIABETES MELITUS TIPE 2 DI SMAN 3 CIMAHI - Azzahra, Francisca; Karjatin, Atin (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: Diabetes melitus does not only occur in adulthood, but also occurs in adolescence. Data in Indonesia in 2018 with Diabetes melitus patients with the age category of 15 years amounted to 159,014 people. The number of cases in Cimahi City in 2018 was 3,601 cases, thus the need for knowledge of adolescents regarding the prevention of Diabetes melitus, so as to reduce the morbidity rate of non-communicable diseases. Based on the results of the research, animated video educational media can increase adolescent knowledge. Objective: To determine the feasibility of